2017
DOI: 10.1155/2017/1435348
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Cohort Study on Delayed-Onset Infections after Mandibular Third-Molar Extractions

Abstract: Objectives The purpose of the present study was to investigate the occurrence and clinical features of delayed-onset infections after mandibular third-molar extractions. Method and Materials An observational cohort study was conducted on 179 patients undergoing mandibular third-molar extraction between January 2013 and December 2015, for a total of 217 extractions. Data were recorded at the time of extraction (T0), on suture removal seven days later (T1), and 30 days after the extraction, when patients were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
6
19
1
1
Order By: Relevance
“…Results have been conflicting concerning the occurrence of bacteremia after dental procedures; antimicrobial prophylaxis before an invasive dental procedure does not prevent bacteremia, although it can decrease both its magnitude and its persistence [142]. Delayed-onset infections (DOI) after mandibular third molar extractions are rare complications and usually occur about 30 days after the extraction, but they may also develop much later on [143]. The bacteria identified in DOI are Fusobacterium, Prevotella, Bacteroides, and Peptostreptococcus.…”
Section: Infections Associated To Craniofacial Skeletonmentioning
confidence: 99%
“…Results have been conflicting concerning the occurrence of bacteremia after dental procedures; antimicrobial prophylaxis before an invasive dental procedure does not prevent bacteremia, although it can decrease both its magnitude and its persistence [142]. Delayed-onset infections (DOI) after mandibular third molar extractions are rare complications and usually occur about 30 days after the extraction, but they may also develop much later on [143]. The bacteria identified in DOI are Fusobacterium, Prevotella, Bacteroides, and Peptostreptococcus.…”
Section: Infections Associated To Craniofacial Skeletonmentioning
confidence: 99%
“…Nevertheless, sometimes persistent subacute and chronic infections occur, where adequate therapy can be a great challenge for practitioners and where treatment can take a long time [ 6 ]. Especially, delayed-onset wound infections after third molar extraction, which occur several weeks after suture removal and after discharge [ 7 ], can cause varying symptoms affecting hard and soft tissues [ 7 , 8 , 9 , 10 , 11 ]. Figueiredo et al reported that those infections are normally caused by anaerobic bacteria of the oral flora, e.g., Fusobacterium, Peptostreptococcus , Porphyromonas, and Prevotella strains, which in most cases can be successfully treated with combinations of surgical revision and antibiotics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cases of osteomyelitis of the jaw after third molar surgery have been previously described [ 14 ]. As delayed-onset infections occur only several weeks post-intervention [ 7 , 10 ], other diseases of non-odontogenic origin like atypical mycobacteriosis, tuberculosis, or cat scratch disease, which can present with similar symptoms, also have to be taken into account [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include angulation of the impacted teeth, 6 use of oral contraceptives, 6 multiple extractions (both right and left third molars), 7 female sex, 8 heavy smoking, 9 and the absence of antibiotic prescription. 10 The use of antibiotics to prevent postoperative infection after third molar surgery is highly debated, with systematic reviews and meta-analyses reporting on both the effectiveness and ineffectiveness of antibiotics in preventing infections. 12 Evidence on the effectiveness of antibiotics in preventing infections after third molar surgery is crucial, as it has been previously shown that short-term antibiotic treatment could lead to persistence of resistant gut bacteria.…”
Section: Introductionmentioning
confidence: 99%